Considerations Regarding Quality Management in Services as a Marketing Instrument for Increasing Customers' Satisfaction in Tourism Products - Nicolae Teodorescu; Aurelia–Felicia Stancioiu; Augustin Mitu (Amfiteatru Economic Journal, 2009)
The development of service sector – as a defining trait of modern market economy – demands permanent improvement of theory and applications in the domain of quality. Following this statement one can notice a considerable evolution of the advanced approach associated to the concept of quality management in services of specialists bringing to attention modalities and instruments that are more and more sophisticated with the intention to give consistent answers to the management teams of all activities included in the field of services. In this context modern marketing is able to give specialists from academic or real economic environment scientific fundamental approaches that are capable to bring closer together the desired efficiency and efficacy to real consumers' requests and perceptions. The quality management approach at tourist's services level underlines important particularities, creating a symbiosis between percepts and theoretical concepts and the practical need to fundament decisions in the tourist's services quality management. In a modern vision these are approached gradually, in four steps: quality control, quality insurance, total quality control and total quality management. For each step are specified the operational type of quality, level of approach considering marketing activities and users typology. According to each step of knowledge there are developed the instruments, techniques and work methods, fact that amplifies the opportunities to detail this kind of approaches to operational level – with special address to tourism management.
Keywords: M31; L83; M10; 330; quality; quality management; marketing; customer satisfaction